Analisis Pengaruh Debt Covenant, Growth Opportunities, Dan Profitabilitas Terhadap Konservatisme Akuntansi Pada Perusahaan Manufaktur Tahun 2016-2021 - Ilham Firmansyah Hartyawan; Andi Kartika (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to analyze fundamentals that affect stock returns including CR, DER and ROA and to test whether stock prices are able to moderate the relationship between these variables. This research was conducted on food and beverages companies listed on the Indonesia Stock Exchange from 2016 to 2020. The data used is the financial report (annual report). The sampling method used purposive sampling method. Test to see the effect using multiple linear regression analysis. The results showed that CR had a significant negative effect on stock returns. DER has a significant positive effect on stock returns. ROA has a significant negative effect on stock returns. Stock prices are able to moderate the relationship of CR, DER and ROA to stock returns with a weakening function. The coefficient of determination test shows that CR, DER and ROA are able to provide an overview of changes in stock prices of 63.9% and the remaining 36.1% is influenced by other variables outside the study. Keywords : Current Ratio, Debt To Equity Ratio, Return On Assets, Stock Return, Stock Price